2011
DOI: 10.1016/j.ajpath.2010.11.024
|View full text |Cite
|
Sign up to set email alerts
|

XB130, a Novel Adaptor Protein, Promotes Thyroid Tumor Growth

Abstract: Adaptor proteins with multimodular structures can participate in the regulation of various cellular functions. We have cloned a novel adaptor protein, XB130, which binds the p85␣ subunit of phosphatidyl inositol 3-kinase and subsequently mediates signaling through RET/ PTC in TPC-1 thyroid cancer cells. In the present study, we sought to determine the role of XB130 in the tumorigenesis in vivo and in related molecular mechanisms. In WRO thyroid cancer cells, knockdown of XB130 using small interfering RNA inhib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
84
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(89 citation statements)
references
References 38 publications
(47 reference statements)
3
84
0
Order By: Relevance
“…Growth of tumors in nude mice formed from XB130 shRNA stably transfected WRO cells were significantly reduced, with decreased cell proliferation and increased apoptosis [12]. In the present study, we found that knockdown of XB130 inhibited invasion and mobility in OS cells in vitro, but the molecular contribution of XB130 in lung metastasis of OS cancer is still unknown.…”
Section: Discussionmentioning
confidence: 53%
See 2 more Smart Citations
“…Growth of tumors in nude mice formed from XB130 shRNA stably transfected WRO cells were significantly reduced, with decreased cell proliferation and increased apoptosis [12]. In the present study, we found that knockdown of XB130 inhibited invasion and mobility in OS cells in vitro, but the molecular contribution of XB130 in lung metastasis of OS cancer is still unknown.…”
Section: Discussionmentioning
confidence: 53%
“…XB130 has been detected in human esophageal squamous cell carcinoma (ESCC) [11], follicular and papillary thyroid carcinoma, as well as in human lung carcinoma cell lines [12]. In ESCC cells, expression of XB130 may affect cell cycle progression and impact prognosis of patients with ESCC [11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…As previously mentioned, XB130 expression could be detected in various normal tissues of human including spleen, thyroid, kidney, lung, brain and pancreas (54). The expression of XB130 was detected in normal esophageal glands and in the cytoplasm of thyroid follicular cells in normal thyroid tissue, and no expression was identified in the normal epithelium (48,49,54). These findings indicate that XB130 may have an important role in normal glandular apparatus.…”
Section: Mechanism Of Xb130 In Cancermentioning
confidence: 53%
“…Shiozaki et al (48) found that XB130 was highly expressed in human thyroid cancers. The in vitro study by Lodyga et al (49) of the TPC1 cell line identified that downregulation of XB130 in the TPC1 cell line derived from papillary thyroid carcinoma led to proliferation reduction and anoikis promotion.…”
Section: Xb130 In Cancermentioning
confidence: 99%